A novel chemiluminescent immunochromatographic assay strip for rapid detection of mercury ions. Issue 16 (12th April 2017) - Wang, Xiaomei; Liu, Fengquan; Shao, Qian; Yin, Zhengrong; Wang, Limin; Fu, Zhifeng
Abstract : A chemiluminescent immunochromatographic assay strip for rapid detection of Hg 2+ was developed by using an anti-Hg 2+ monoclonal antibody that could directly recognize Hg 2+ . Abstract : Mercuric ions (Hg 2+ ) have long been regarded as one of the most hazardous environmental pollutants with adverse effects on environmental safety and serious toxic effect on human health. In the present work, an anti-Hg 2+ monoclonal antibody (anti-Hg 2+ Mab) was prepared, which could directly recognize Hg 2+ without the need for a chelator. This antibody was used to develop a chemiluminescent (CL) immunochromatographic assay strip (ICAS) for rapid, facile, specific and sensitive detection of Hg 2+ . A conjugate of ovalbumin and Hg 2+ (OVA–Hg 2+ ) adopted as a coating antigen was immobilized on a nitrocellulose membrane to assemble a test line of the developed ICAS. The anti-Hg 2+ Mab was tagged with horseradish peroxidase (HRP) and deposited onto the conjugate pad of the ICAS to act as a signal tracer. After introduction of the sample solution containing Hg 2+, the immobilized OVA–Hg 2+ conjugate competed with Hg 2+ in the sample solution to bind with HRP-tagged anti-Hg 2+ Mab. Afterward, a CL reaction signal catalyzed by the bound HRP was collected to quantitate the level of Hg 2+ in the sample solution. Under optimal conditions, the linear range for Hg 2+ detection was 1.0–100 ng mL −1, with a detection limit of 0.2 ng mL −1 (S/N = 3). The whole detection procedure could be accomplished within 18 min. The recovery values of Salvia Miltiorrhiza and lake water samples spiked with Hg 2+ were 94.5–114.8% and 88.0–90.0%, respectively, showing acceptable reliability for real sample detection.